Analytical Method Development for Sodium Valproate through Chemical Derivatization - Murad Abualhasan; Nihaya Wasif Odeh; Ghadeer Naser Younis; Oyoun Fadel Zeidan (International Journal of Analytical Chemistry)
Background. Sodium valproate has anticonvulsant activity and is structurally different to conventional antiepileptic drugs. The problem with valproic acid is the lack of a chromophore, which means that gas chromatography is the sole assay methodology. The introduction of benzoyl and phenyl groups to the molecule is a useful derivatisation, which enables the creation of detectable chromophores for HPLC analysis for pharmaceutical dosages as well as biological systems. Methodology. Sodium valproate was derivatised by the addition of a chromophore to its structure by introducing a methyl benzoyl or a phenyl group. Trichlorophenol and 2-hydroxyacetophenone were used to introduce phenyl and benzoyl groups to valproic acid, respectively. The reaction used was estrification reaction using coupling agents. An analytical method was then developed and validated using reverse-phase HPLC. The method was validated for parameters like linearity, range, accuracy precision, and robustness. Results. The developed method was easy and feasible and can be applied to both routine analysis and bioanalysis. The method was very sensitive and could quantify valproic acid at a very low concentration of 0.75 × 10−5 mg/ml. The developed method was found to be linear (R2 = 0.997), accurate, precise, and robust. Conclusion. The proposed chemical derivatisation and the developed analytical method are novel. The developed analytical procedure is the first of its kind; it is easy and feasible and can be used to quantify and detect sodium valproate at very low concentrations compared to other available methods in the literature.